Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak UMKM di Kota Tanjungpinang - Teddy Haryadi; Nurul Yusyawiru (Jurnal Informatika Ekonomi Bisnis, 2023)
This research examines the influence of moral understanding and moral obligations on tax compliance with socialization as moderation for MSMEs in the Tanjungpinang City area. This research analyzes primary questionnaire data from 100 MSME respondents' answers in the Tanjungpinang City area. Testing research variables uses multiple linear regression analysis and moderated regression analysis (MRA). Moral obligations influence taxpayer compliance. Meanwhile, taxpayer understanding has no effect on taxpayer compliance. And socialization can moderate taxpayers' understanding and moral obligations towards mandatory compliance. The research results are expected to be taken into consideration by tax authorities to increase tax socialization to increase taxpayer compliance.